Localization of Autophagosome in Porcine Follicular Cumulus-oocyte Complex - Seunghoon Lee; Dong-Hoon Kim; Gi-Sun Im; Sun-A Ock; Imran Ullah; Tai-Young Hur (The Korean Society of Animal Reproduction and Biotechnology, 2017)
Autophagy is an intracellular degradation and recycling system. Oocyte maturation is dynamic process, in which various proteins should be synthesized and degraded. In our previous study, we reported the loci of autophagosome and dynamics of autophagic activity in porcine oocytes during In Vitro maturation. In this study, we verified loci of autophagosome in porcine follicular cumulus-oocyte complex by detection of microtubule-associated protein 1A/1B-light chain 3 (LC3) which is the reliable marker of autophagosome. Porcine ovary including various sizes of follicles was fixed within 1 hour after collection from slaughterhouse. After fixation, immunohistochemistry was conducted on sliced ovary tissue containing various sizes of follicles by using LC3 antibody. As a result, LC3 signal was clearly detected in both cumulus and oocytes of various sizes of follicles. We also found ring shaped signal which represent autophagosome near oocyte membrane. Most of the signals in oocytes were localized nearby cellular membrane while evenly dispersed in cumulus cells. Therefore, this result suggests that autophagy occurs in porcine COCs (cumulus-oocyte complexes) at follicular stage.